Development of Motorized Board of Wheelchair Using Arduino Controller - Hashim, Hairulazwan; Mustafa, Muhammad Azmi (Progress in Engineering Application and Technology, 2020)
In the present world, there a lot of robots that been used to make human life easier as it plays an important role not even in the industry but also in our personal lives. This idea was applied in healthcare industries as its responsibility to improve the quality of cares and saving patient lives. This paper presents an overview of the Development of Motorized Board of Wheelchair Using Arduino Controller. This project aims to make an automated wheelchair in the market becomes noticeable and widely use to help patients with current technologies. It also gives freedom for those that have difficulty in using a manual wheelchair with suitable technology and design in term of comfortability, accessibility, functionality and affordability. This project was designed by using SolidWorks 2016 for the body hardware and Fritzing software for the circuit. This project used two DC power window motor to drive the wheels and by using triple-axis accelerometer breakout ADXL335 as the controller to steering the movement of the wheelchair. This project also equipped with wireless communication between the receiver and transmitter by using the HC-12 UART as the interfaces. Additionally, the user is free to choose a suitable chair according to their situation of sickness and comfortability. As a result, the dimension of this prototype chassis is 800 mm (length) x 600 mm (width) x 710 mm (height) with 9 kg of weight, and the average maximum speed is 1.98 km⁄h without load.